Perancangan Dan Implementasi Sistem Monitoring Ketinggian Banjir Berbasis Web Dan IoT (Internet Of Things) Menggunakan Sensor Ultrasonik - Siti Sundari; Muhammad Jafar Siddik Simanjuntak; Yuyun Dwi Lestari (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Indonesia has two seasons, wet and dry. During the rainy season, rain can occur at high intensity and cause floods. Add another clogged drain to the river caused by the garbage. A flood can cause both material and life damage. It is necessary to inform the public about the hight discharge of water as an erly warning, so that people can prepare for the flood. The web-based high-altitude monitoring system and the IoT uses ultrasonic sensors if efficient to provide high water information to the public. It will read the water level with an ultrasonic sensor and will transmit realtime water-discharge information over the internet to the website. For the system to work as it would like, NodeMCU must be connected to the internet. All data read by the sensor will be displayed and stored in the thingspeak database.